Social entrepreneurship : from issue to viable plan - Barreiro, Terri D.; Stone, Melissa M. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
This book provides a guided deep dive into the early stages of venture development of social entrepreneurship. It introduces concepts that provide important insights necessary for social venture success. It introduces a set of entrepreneurial tools designed for the unique set of challenges faced in selecting and designing social entrepreneurial ventures. With this book as a guide, the reader can develop a feasible venture concept and communicate it effectively.
1. Introduction -- 2. Issues, ideas, and opportunities, a simultaneous pursuit -- 3. Understanding those to be served and their communities -- 4. The policy environment, opportunities and constraints -- 5. Analyzing competitive forces, the market and the industry -- 6. Creating a social venture feasibility plan -- 7. Completing a viability assessment of the venture -- Appendix I. Denise DeVaan: from teacher to national advocate reducing poverty -- Appendix II. Frey Foundation (Minnesota): a story of a journey from charity to systems change engagement -- Appendix III. Mike Temali: expert in neighborhood and economic transformation -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (pages 117-120) and index.
Title from PDF title page (viewed on September 27, 2013).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Social entrepreneurship; social entrepreneurship; feasibility analysis; entrepreneur; social entrepreneur; theory of change; logic model; public policy analysis; nonprofit; Electronic books